1996
DOI: 10.1021/jp951999t
|View full text |Cite
|
Sign up to set email alerts
|

Singlet and Triplet State Back Electron Transfer from Photogenerated Radical Ion Pairs Studied by Time-Resolved CIDNP

Abstract: Radical ion pairs are generated in acetonitrile solution by photoinduced electron transfer from naphthalene derivatives to cyanobenzenes and undergo reverse electron transfer to the singlet ground and to excited triplet states of the parent compounds. Both pathways lead to chemically induced nuclear polarization of the ground state products. They can be separated because the triplet contribution appears delayed by the triplet lifetime. Variation of the radical pair energy leads to a dominance of either the sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The triplet state of the excited 1,4dimethoxynaphthalene molecule is lower in energy than the radical-ion pair; therefore, by changing the concentration of fumaronitrile, one can change the multiplicity of the radical pair. 53 The measurement of the DEE rate constants can be markedly simplified by proceeding from the dependence of the DNP kinetics on the concentration of the diamagnetic product. This method has advantages over investigation of the concentration dependence of the half-with of the DNP spectra because the half-width of the spectra depends appreciably on the amplitude of the RF field B 1 , whereas the DNP kinetics do not.…”
Section: Dynamic Nuclear Polarisation In Radical Ionsmentioning
confidence: 99%
“…The triplet state of the excited 1,4dimethoxynaphthalene molecule is lower in energy than the radical-ion pair; therefore, by changing the concentration of fumaronitrile, one can change the multiplicity of the radical pair. 53 The measurement of the DEE rate constants can be markedly simplified by proceeding from the dependence of the DNP kinetics on the concentration of the diamagnetic product. This method has advantages over investigation of the concentration dependence of the half-with of the DNP spectra because the half-width of the spectra depends appreciably on the amplitude of the RF field B 1 , whereas the DNP kinetics do not.…”
Section: Dynamic Nuclear Polarisation In Radical Ionsmentioning
confidence: 99%
“…Quenching of singlet aromatic amines by ground state acceptors can also result in electron transfer. In comparison to the quenching of singlet acceptors by aromatic amines, quenching of singlet aromatic amines by ground state acceptors has received limited attention. Beens and Weller 1a noted the failure of dimethylaniline and benzene to form an exciplex and suggested that it might be a consequence of limited orbital overlap.…”
mentioning
confidence: 99%
“…At the initial stages, we could see only the characteristic absorptions of 3 (ZnP(TPA) 3 )* at 480 and 820 nm, suggesting that the intersystem crossing (ISC) process from 1 (ZnP(TPA) 3 )* occurs after the fast charge-separation and charge-recombination processes in the picoseconds time region. Such fast intersystem crossing (ISC) processes were reported in compact donor−acceptor molecules, especially when the donor is placed to be nearly in perpendicular orientation to that of the acceptor. With the decay of 3 (ZnP(TPA) 3 )*, the absorption bands appeared at 480, 770, and 1310 nm as seen in the transient spectra in the microsecond region (inset of Figure ). This observation demonstrates the generation of (ZnP(TPA) 3 ) •+ −(SubPc(F) 12 ) •− via 3 (ZnP(TPA) 3 )* in benzonitrile.…”
Section: Resultsmentioning
confidence: 85%